KONSUMSI LISTRIK DAN PERTUMBUHAN EKONOMI DI INDONESIA, 1995-2015 - Febryta Aldila Shinta D.; Ahmad Zafrullah TN.; Firman Rosjadi Djoemadi (Perpustakaan Universitas Surabaya, 2018)
The paper seeks to analyze the relationship between electricity consumption and economic growth in Indonesia using Granger Causality Test method. The study also applied ADF UnitRoots Test and Johansen Cointegration Test to ascertain the stasionerity and the relationship between variables that was examined. This paper’s study used time series datas in the period 1995-2015. Based on results, the study found the existence of significantly impact of the variables on economic growth. This study also showed an evidence of one-directional causal relationship between electricity consumption and economic growth.